The quality of the Mars Phoenix pressure data. (February 2020) - Kahanpää, Henrik; Polkko, Jouni; Daly, Michael
Abstract: The Phoenix lander operated on the surface of Mars for circa 5 months in 2008. One of its scientific instruments is an atmospheric pressure sensor called MET-P. We perform a comprehensive study to identify all error sources affecting the data measured by MET-P and to generate methods for compensating these errors. Our results show that MET-P performed much better than was reported immediately after the mission (Taylor et al., 2010). The error limits of the original calibrated Phoenix pressure data currently available in NASA's Planetary Data System (Dickinson, 2008) are from −5.3 ​Pa to +3.5 ​Pa. Further, almost no temperature-dependent error exists in the original calibrated MET-P data. However, we identify a previously unknown error source, temperature hysteresis, which causes minor peaks in the measured pressure curve (<0.4 ​Pa). A version of the Phoenix pressure data generated by applying all the error compensations developed in this study is available on Mendeley Data (Kahanpää et al., 2019). The study is based on the re-analysis of the original test data of MET-P, the analysis of the engineering data measured during the mission on Mars and during the interplanetary cruise, and laboratory tests with the Reference Model of the MET-P sensor. Temperature dependent errors are evaluated by comparing the readings of two sensor heads with different sensitivities, measuring the same quantity. The principle of this method is applicable also for other types of instruments. Highlights: The quality of the atmospheric pressure data of the Mars Phoenix lander is studied. The data are more accurate than reported before. A corrected version of the data is available on Mendeley Data. There are almost no temperature-dependent errors. Temperature hysteresis causes small deviations.